Combined STEM-EDS tomography of nanowire structures. (17th October 2019) - Bender, Hugo; Richard, Olivier; Kundu, Paromita; Favia, Paola; Zhong, Zhichao; Palenstijn, Willem Jan; Batenburg, Kees Joost; Wirix, Maarten; Kohr, Holger; Schoenmakers, Remco
Abstract: The 3D spatial resolution, the material contrast and the evolution of the noise are analyzed in the reconstructed volume of a combined scanning transmission electron microscopy (HAADF-STEM) and energy dispersive x-ray spectroscopy (EDS) tomography experiment. Standard simultaneous iterative reconstruction technique and HAADF-EDS bimodal tomographic reconstruction are considered for the +/−90° tomography series of a pillar shaped sample embedding a full nanowire device. With a high number of iterations, a spatial resolution for both HAADF and EDS down to 5 nanometer can be reached for this volume. Best material's contrast and minimum noise are obtained for medium number of iterations. Improvement of the signal-to-noise and contrast can be obtained by filtering the EDS data while the spatial resolution is not impacted. A fast and reliable preparation methodology for rectangularly shaped pillar samples for tomography analysis is discussed.